Neuromuscular Electrical Stimulation Training vs. Conventional Strength Training: A Systematic Review and Meta-Analysis of the Effect on Strength Development. Issue 12 (19th December 2022) - Happ, Kevin A.; Behringer, Michael
Abstract: Happ, KA, and Behringer, M. Neuromuscular electrical stimulation Training vs. conventional strength training: a systematic review and meta-analysis of the effect on strength development. J Strength Cond Res 36(12): 3527–3540, 2022—A systematic review of the current state of literature and a meta-analysis were conducted to compare the strength development between neuromuscular electrical stimulation (NMES) and conventional strength training when training volume is matched. Searches of PubMed and several other databases were conducted for studies that met the following primary inclusion criteria: randomized studies of >20 days duration with a sample size of >4 subjects in each group ("voluntary contraction" [VC] and "electrically stimulated" [ES]) conducted with percutaneous stimulation only in healthy individuals at equal training volume. Finally, a total of 19 studies were included in the analysis. When comparing strength gains between groups (ES-VC), no favorable effect toward a training method could be observed (0.023 hg [95% CI: −0.198 to 0.246, p = 0.836]). Subgroup analyses were performed based on the application type (NMES evoked and NMES onto voluntary contractions) and stimulation frequency. Both analyses revealed no favorable effect and significant difference of groups (significance level set at 0.05). A meta-regression evaluated the relationship between stimulation frequency and effect size difference. The regression showed a tendency of higher stimulation frequencies being associated with higher study effect size differences (predicted effect size = −0.599 + 0.008 (Hz) ( p = 0.176)). The findings indicate that training with NMES results in virtually identical strength gains compared with conventional strength training when training volume is matched. If training with NMES is preferred, the stimulation frequency type (regular or Burst Mode Alternating Current) can be chosen according to preference without loss of effectiveness.